Photodynamic therapy using self-assembled nanogels comprising chlorin e6-bearing pullulan. Issue 32 (20th July 2021) - Kawasaki, Riku; Ohdake, Reo; Yamana, Keita; Eto, Takuro; Sugikawa, Kouta; Ikeda, Atsushi
Abstract : Efficient photodynamic therapy using self-assembled nanogel comprising chlorin e6-bearing polysaccharide. Abstract : With minimal invasiveness and spatiotemporal therapeutic effects, photodynamic therapy is one of the most promising candidates for cancer treatment. Here, we developed a facile self-assembled nanogel using photosensitizer-grafted polysaccharides called chlorin e6-bearing pullulan. Chlorin e6 is used as a photosensitizer in cancer therapy. The anti-cancer effect of photodynamic therapy with our nanogel system was 780 times higher than that of the commercially available photosensitizer Photofrin. Finally, we demonstrated that actively growing cancer cell spheroids can be completely suppressed after treatment. Our system could efficiently induce tumor regression in tumor xenograft mice.